Simulation on the effects of the Arduino PID controller parameters using the WOKWI online simulator - Djoko Untoro Suwarno (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
PID controllers are known in the industrial world as reliable controllers and are studied in universities. The explanation of the ideal PID mathematically often makes it difficult for students to understand the computational process and the implementation that occurs. Often there is difficulty in selecting the correct controller parameters, for example, the Kp, Ki, and Kd parameters. In this study, PID parameters were selected in the form of Kp, Ti, and Td and observed controller output. The Ti parameter as the time integral is easier to understand than the Ki parameter as the gain integral. The Arduino simulator used is wokwi which is an online Arduino simulator. The PID library used is the Arduino Brett Beauregard PID. The results obtained are the effect of changes in the parameters of Kp, Ti, and Td on the controller output. For larger Kp, the controller output is proportional to the amount of input. The larger the Ti, the slower the system output, while the effect of Td is used when the input changes frequently